HUMAN DEVELOPMENT INDEX AND LITERACY: BALANCE OF EDUCATION QUALITY WITH EQULIBRIUM THEORY - Aprilliantoni Aprilliantoni (Almarhalah | Jurnal Pendidikan Islam, 2021)
AbstractIn the current era of globalization, competition between countries is getting stronger and is determined by the quality of their human resources. One of the benchmarks is the Human Development and Literacy Index. The better the HDI number, the better the quality of the country's human resources, thus also literacy rate. However, the country of Indonesia, which is so vast and consists of thousands of islands, leaves a serious problem, namely the high inequality of HDI figures and the low numbers literacy of the people.This paper offers a discussion and a solution for increasing the development of Human Resources and Literacy with equilibrium theory in microeconomics, to overcome inequality which is currently a serious problem. This is of course in accordance with the constitutional mandate of "Social Justice for All Indonesian People" as a reference paper based on authoritative literature with social, economic and educational analysis.Key word : Human Development Index, Literacy, Equlibrium Theory